Beyond finance: Impact of Islamic finance on economic growth in Pakistan - Huma Nawaz; Maira Abrar; Asma Salman; Syed Muhammad Hassan Bukhari (Universitas Islam Indonesia, 2019)
Islamic finance, which may have been considered only in the context of a multitude of trading structures among economists, merits a fresh evaluation in how it dovetails with and supports national economic growth. This study examines the dynamic interaction between Islamic financing and economic growth of Pakistan by employing the unit root test, cointegration test and Granger Causality tests to see whether the Islamic financial system influences the economic growth. For the analysis, time series data of total Islamic financing and real GDP per capita, Islamic financial assets, and population to represent real economic sector were considered. Findings/Originality: This paper finds that a well-functioning Islamic financial system promotes economic growth. It also finds an evidence of a bidirectional relationship between Islamic asset financing and population. It implies that population reinforces Islamic finance, and population attracts Islamic financing.